Cyclic loading behavior on strengthened composite beams using external post-tensioning tendons (experimental study). (February 2021) - Hassanin, Ahmed Ibrahim; Shabaan, Hesham Fawzy; Elsheikh, Ahmed Ibrahim
Abstract: In recent years, due to corrosion and the constant demand for increased traffic flow, it emerged that there is a need for an efficient system that can be used to repair and / or strengthen bridges and structures with steel–concrete composite section. There have been many strengthening techniques used to prevent such serious structural problems. One of these techniques, which has proven effective in repairing and strengthening structural members, is to use externally post-tensioned tendons. This study provides a recently completed experimental program on scaled bridge composite steel–concrete beams strengthened with external post-tensioning tendons to investigate the fundamental cyclic loading behavior. In addition to studying the effect of the strengthening system, there was another major factor under study which was the degree of shear connection. The study mainly relied on testing the beams under the influence of cyclic loads in addition to changing the degree of shear contact. Reducing the degree of shear connection simulates a form of composite action loss of composite beams due to cyclic loads. The study results provides modes of failure, characteristic points, load–deflection curves, slip between steel beam top flange and the concrete flange, the shear connector strains, and the concrete and steel beam bottom flanges strains. Based on the experimental results, adding external post-tensioning enhanced the overall performance of the composite beams under cyclic loading by significantly reducing strains of the shear studs, the concrete flange, and the steel I-beam at all loading stages. The strengthened specimens experienced an increase in the ultimate capacity and residual stiffness comparable to non-strengthened specimens, attributable to significant loss of composite action between concrete flange and steel beam through cyclic load test.